Penerapan model pembelajaran time token berbantuan media question card untuk meningkatkan hasil belajar matematika pada materi geometri keliling dan luas bangun datar kelas V sekolah dasar - Laili Nabilah; Matsuri Matsuri (Universitas Sebelas Maret, 2025)
This study aims to improve the mathematics learning outcomes of fifth grade students of SDN Beskalan Surakarta on the material of the perimeter and area of flat shapes through the Time Token learning model assisted by question card media. The research was conducted in the form of Classroom Action Research (PTK) for two cycles. Data collection techniques include observation, interviews, tests, and documentation, with qualitative and quantitative analysis. The results showed an increase in teacher and learner activities in each cycle. The completeness of learning outcomes increased from 25.93% in pre-action to 88.89% in cycle II. The application of the Time Token model proved effective in increasing active participation and understanding of geometry concepts. This research reinforces the importance of active learning models that involve interesting media in supporting the improvement of learning outcomes in elementary schools.